The 2013 International Joint Conference on Neural Networks (IJCNN) 2013
DOI: 10.1109/ijcnn.2013.6707016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization measures of ensemble systems using a meta-learning approach

Abstract: In a decision making process, we are usually oriented to take into consideration all the relevant features (characteristics) involved in a specific problem. In Machine Learning, for instance, a decision is made through the use of a learning algorithm and the characterization process is represented by the corresponding datasets. In this context, classification algorithms can be applied, individually or through the use of ensemble systems (combination of classification methods), in the decision-making process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Na literatura, diversos trabalhos têm investigado meta-aprendizagem de maneira mais profunda em tarefas de classificação e regressão e tem sido aplicadaà recomendação de algoritmos em uma gama de domínios de aplicações, como seleção de modelos de séries temporais [Prudêncio and Ludermir 2004] e medidas de caracterização de comitês [Parente et al 2013].…”
Section: Meta-aprendizagem Aplicadaà Seleção De Algoritmosunclassified
“…Na literatura, diversos trabalhos têm investigado meta-aprendizagem de maneira mais profunda em tarefas de classificação e regressão e tem sido aplicadaà recomendação de algoritmos em uma gama de domínios de aplicações, como seleção de modelos de séries temporais [Prudêncio and Ludermir 2004] e medidas de caracterização de comitês [Parente et al 2013].…”
Section: Meta-aprendizagem Aplicadaà Seleção De Algoritmosunclassified
“…In the literature, several studies that use meta-learning to recommend algorithms can be found, such as in [15], [13], [16], [17] and [18]. However, although there are several relevant studies, it is clear that there is a lack of investigation towards the possibility of using recommendation methods to assist in effectively defining the main parameters of an ensemble, notably the classifier type, the number of classifiers and the combination methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ensemble systems, very little effort has been done to use meta-learning as a recommendation tool in the automatic design of these systems [8], [9]. In [8], for instance, it is presented an approach to create customized model ensembles on demand, inspired by Lazy Learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the approach proposed in [8] does not apply meta-learning on the recommendation level of configuration parameters for an ensemble system, unlike the methodology we apply in this paper. In addition, in [9], the authors combined the idea of meta-learning with ensemble systems, with the goal to help the design of efficient and robust ensemble systems. However, they recommended different parameters of an ensemble systems (size and structure) of the one we recommend in this paper (ensemble architecture and individual classifiers) and they used different metalearning methodology (meta-features and meta-learner).…”
Section: Introductionmentioning
confidence: 99%